Analysis of Occlusal Vertical Dimension and Mandibular Basal Bone Height in a Nigerian Population. (1st October 2014) - Akinbami, Babatunde O.; Nsirim, Prince E.
Abstract : Background . The actual basal bone height of the reconstructed mandible is relevant to achieve normal occlusal vertical dimension for the prosthesis fabricated. The purpose of the study was to determine the mean and baseline values of the occlusal vertical dimension and height of the mandibular basal bone in a Nigerian population. Method . Each participant was asked to bring the upper and lower teeth into contact, while the distance between the nasal sill and dimple on the lower lip was measured (OVD). The skin at lower border of the mandible was marked and the distance between this point and the landmark on the lower lip was measured, MBH. Result . 200 subjects were evaluated. Age range was 16–30 years, mean± (SD), 21.6± (3.1) years. Males had mean ± (SD) of 42.10± (5.34) mm for OVD and females 39.72± (5.25) mm; acceptable baseline range of OVD for any population will be 34–48 mm (3.4–4.8) cm. All the males had a mean± (SD), 30.54± (6.13) mm for MBH, and all the females 29.63± (5.23) mm. Acceptable baseline range of MBH for any population will be 24–37 mm (2.4–3.7) cm. Conclusion . To reconstruct the mandible and still maintain the OVD, heights of bone grafts must not be less than 2 cm or greater than 4 cm.